Analysis Tax Regulation MoF 79/2023: Assessing Legal Certainty & Justice in Regulation and Practice - Priyono, Agus Puji; Nisa, Farhatun (Politeknik Ganesha Medan, 2024)
The fundamental principles of justice and legal certainty are integral components of the rule of law, concerning the protection of individual rights, specifically in taxation. In this context, the importance of regulation demands the presence of strong legal values. Legal certainty guarantees clear rules, protects rights, and promotes trust in the judicial system. The enactment of Minister of Finance (MoF) Regulation Number 79 of 2023 serves as a responsive measure to the demands for adaptive tax regulations due to the evolution of laws. Therefore, this research aimed to analyze MoF Regulation Number 79 of 2023 using qualitative methods to explore and understand the meaning of taxpayers' perspectives relating to assessment procedures in regulation and practice to provide in-depth guidance on assessment in taxation. MoF Regulation Number 79 of 2023 is important for tax system compliance, justice, and legal certainty, serving as a multi-faceted juridical, philosophical, and sociological foundation. The results show that the regulation adheres to legal principles, influencing taxation practices regarding tangible and intangible assets, income tax, Value Added Tax (VAT), and sale agreements. Practical aspects, including the Indonesian Professional Appraisal Society (MAPPI) relationship, professional judgment, and considerations for business dissolution, enhance justice, legal certainty, and tax compliance. Moreover, future research can analyze the latest regulations issued as a theoretical and practical foundation for taxpayers, aid in setting valuation standards, and ensure compliance with the changing law for the professional practice of tax experts and accountants.